The Tissue Distribution of SARS-CoV-2 in Transgenic Mice With Inducible Ubiquitous Expression of hACE2 - Dolskiy, Alexander A.; Gudymo, Andrey S.; Taranov, Oleg S.; Grishchenko, Irina V.; Shitik, Ekaterina M.; Prokopov, Dmitry Yu; Soldatov, Vladislav O.; Sobolevskaya, Elvira V.; Bodnev, Sergey A.; Danilchenko, Natalia V.; Moiseeva, Anastasia A.; Torzhkova, Polina Y.; et al. (Frontiers in Molecular Biosciences, 2022)
The novel coronavirus disease COVID-19 has become one of the most socially significant infections. One of the main models for COVID-19 pathogenesis study and anti-COVID-19 drug development is laboratory animals sensitive to the virus. Herein, we report SARS-CoV-2 infection in novel transgenic mice conditionally expressing human ACE2 (hACE2), with a focus on viral distribution after intranasal inoculation. Transgenic mice carrying hACE2 under the floxed STOP cassette [(hACE2-LoxP(STOP)] were mated with two types of Cre-ERT2 strains (UBC-Cre and Rosa-Cre). The resulting offspring with temporal control of transgene expression were treated with tamoxifen to induce removal of the floxed STOP cassette, which prevented hACE2 expression. Before and after intranasal inoculation, the mice were weighed and clinically examined. On Days 5 and 10, the mice were sacrificed for isolation of internal organs and further assessment of SARS-CoV-2 distribution. Intranasal SARS-CoV-2 inoculation in hACE2-LoxP(STOP)×UBC-Cre offspring resulted in weight loss and death in 6 out of 8 mice. Immunostaining and focus formation assays revealed the most significant viral load in the lung, brain, heart and intestine samples. In contrast, hACE2-LoxP(STOP)×Rosa-Cre offspring easily tolerated the infection, and SARS-CoV-2 was detected only in the brain and lungs, whereas other studied tissues had null or negligible levels of the virus. Histological examination revealed severe alterations in the lungs, and mild changes were observed in the brain tissues. Notably, no changes were observed in mice without tamoxifen treatment. Thus, this novel murine model with Cre-dependent activation of hACE2 provides a useful and safe tool for COVID-19 studies.